(untitled) (Journal of Geography and Environmental Management, 2023)
This article is devoted to the development and use of the natural environment for ecotourism purposes, which is one of the most actual problems of our time. In this context, the development of such types of nature conservation tourism, such as eco-tourism, is a particularly important task. Besides, ecotourism today represents one of the fastest growing sectors of the world industry of tourism. Kazakhstan possesses big possibilities for organization of this kind of tourism. In particular, Southern Kazakhstan is the most attractive from the ecotourist point of view. Therefore, the authors have carried out work on an assessment of the potential of tourist and recreational resources of Southern Kazakhstan for the purposes of ecotourism development. The relevance of the theme of the study increases due to the fact that South Kazakhstan, with its great potential for the development of ecotourism, is at the same time the most densely populated region of Kazakhstan. Therefore, the development of ecotourism in this region should be considered as one of the priority ways to reduce the negative impact on ecological systems as a result of tourism activities. In this article natural and socio-economic recreational resources of ecotourism are analyzed and systematized, and also zoning of considered region on a degree of saturation by objects of tourist service is conducted, the total tourist-resource potential on which basis perspective areas on development of ecotourism are defined, the attractiveness map of tourist-recreational resources of Southern Kazakhstan is made.